2021
DOI: 10.1080/14787210.2021.1939683
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs/nitazoxanide/azithromycin repurposed for COVID-19: potential mitigation of the cytokine storm interleukin-6 amplifier via immunomodulatory effects

Abstract: Introduction: Mediators of immunity and inflammation are playing a crucial role in COVID-19 pathogenesis and complications as demonstrated by several genetic and clinical studies. Thus, repurposing of drugs that possess anti-inflammatory and/or immune-modulatory effects for COVID-19 is considered a rational approach. Areas covered: We analyze selected studies that correlated COVID-19 with dysregulated interferon and inflammatory responses while reflecting on our academic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 53 publications
0
37
0
2
Order By: Relevance
“…Importantly, other than their suggested potential to cure COVID-19 [7], we also noticed that NSAIDs had remarkably superior symptomatic clinical efficacy compared to paracetamol, as described by those who used paracetamol before switching to the new protocol, for controlling high fever, headache, and malaise. Notably, it was recently suggested that NSAIDs might influence COVID-19 outcomes through modulation of the immune-inflammatory responses rather than modifying susceptibility to infection or viral replication and it was also shown that NSAID treatment did not affect ACE2 expression in human cells and mice nor did NSAIDs affect SARS-CoV-2 entry or replication in vitro, yet NSAIDs were shown to dampen the induction of proinflammatory cytokines that are upregulated by SARS-CoV-2 infection in mice [36] and we agree with their call to assess their effects in humans while suggesting that it is probable to discover beneficial NSAIDs effects on both the humoral and cellular immunity [7].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Importantly, other than their suggested potential to cure COVID-19 [7], we also noticed that NSAIDs had remarkably superior symptomatic clinical efficacy compared to paracetamol, as described by those who used paracetamol before switching to the new protocol, for controlling high fever, headache, and malaise. Notably, it was recently suggested that NSAIDs might influence COVID-19 outcomes through modulation of the immune-inflammatory responses rather than modifying susceptibility to infection or viral replication and it was also shown that NSAID treatment did not affect ACE2 expression in human cells and mice nor did NSAIDs affect SARS-CoV-2 entry or replication in vitro, yet NSAIDs were shown to dampen the induction of proinflammatory cytokines that are upregulated by SARS-CoV-2 infection in mice [36] and we agree with their call to assess their effects in humans while suggesting that it is probable to discover beneficial NSAIDs effects on both the humoral and cellular immunity [7].…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, an objective analysis has found no conclusion of causation between ibuprofen and risk of thromboembolism and when this risk is claimed, it is often associated with long term and/or the use of high doses [53] which is apparently the opposite to what we have adopted. On the contrary, we claim that the anti-IL-6 properties of our adopted short course of NSAIDs might decrease the incidence of thomboemoblism [7,54] and a large study has confirmed NSAIDs safety in COVID-19 management and suggested that the concerned policymakers should review their issued NSAIDs COVID-19 advice [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, though a variable immunological response was suggested to predict mortality in COVID-19 patients and Th2, Th17 cell, and Treg percentages were significantly lower in deceased COVID-19 cases than recovered and healthy control [5], yet COVID-19's high morbidity and mortality were still suggested to be related to low Th1 [6], and spike-specific Th1 cells capable of IL7dependent homeostatic proliferation were shown to predict survival from severe COVID-19 [7]. Similarly, un-sustained effective Th1 response and dominant Th2 response were demonstrated, in a prospective cohort of patients, to be related to a worse COVID-19 prognosis [8], and we suggest that their observed higher levels of IFN-γ related to mortality might be, similar to other types of interferons, induced in critically ill patients in a final futile attempt to tune the untuned antiviral immunity [9] that exacerbate, instead of ameliorate, the induced immunopathic damage [10], and we would like to emphasize defective interferon response as a major culprit responsible for COVID-19 deterioration [11,12]. In another explanation to the various clinical outcomes, ACE2 was suggested to regulate the immune response in SARS and SARS CoV-2 including activation of B cells, macrophages, Th1 cells and the inhibition of Treg cells and CD8 + T cells [13] and ACE2 [14] and other discovered [15] and potentially yet to be discovered genetic polymorphisms e.g.…”
mentioning
confidence: 84%
“…Importantly, since IL-6 has been suggested to play an integral role in the pathogenesis of clinical and experimental viral myocarditis [36,37], we would like to suggest that the potential clinical benefits of few days administration of NSAIDs [38] with SARS CoV-2 vaccines either concomitantly or on the day after both the first and second (if there is one) jabs might eventually exceed the inconclusive potential risk to lower the immune response developed from the vaccines [39].…”
Section: Adenovirus Vectored Vaccines Potential Autoimmunity Riskmentioning
confidence: 99%